PENGARUH KEPUASAN KERJA, KOMPENSASI NON FINANSIAL, SERTA BUDAYA ORGANISASI TERHADAP RETENSI KARYAWAN - Wandara, Diva Ditya Mersita; Wibawa, I Made Artha (E-Jurnal Manajemen; Vol 9 No 5 (2020), 2020)
The purpose of this study is to explain the effect of job satisfaction, non-financial compensation and organizational culture on employee retention. This research was conducted at PT. Bakas Aneka Citra Wisata Tirta with a total sample of 79 employees, the saturated sample method and data collection were carried out through interviews and questionnaires. Data analysis techniques used are the Classic Assumption Test, Multiple Linear Regression, Model Accuracy Test, and Hypothesis Testing. The results of this study indicate that job satisfaction has a positive and significant effect on employee retention, in addition non-financial compensation also has a positive and significant effect on employee retention, and organizational culture has a positive and significant effect on employee retention. Theoretically this research also provides an understanding that by increasing job satisfaction, compensation, and organizational culture it will be able to retain employees to remain in the company. Keywords : job satisfaction, non-financial compensation, organizational culture, employee retention